Study of Bond Issuer Companies Listed on IDX and on PT Pefindo Rating List: The Effect of Financial and Non-Financial Factors on Bond Rating - Dewi Kusumowati; Lebrina Lorince Tangpen (Jurnal Manajemen dan Kewirausahaan, 2022)
The aim of this study is to determine the effect of liquidity, leverage, profitability, bond securities, and maturity variables on bond ratings of entities that issue bonds on the Indonesia Stock Exchange and PT Pefindo's rating list for the period 2019 - 2021. The objects used in this study are all bond issuer companies that have been recorded in PT Pefindo and have complete financial reports on the Indonesia Stock Exchange for 2019 - 2021. There are 11 bond issuer companies used as samples with 3 years of observation so that a sample of 33 is obtained. Sampling is determined by using a purposive sampling, while the insightful strategy utilized is calculated relapse examination. The result shows that liquidity (CR), leverage (DER), profitability (ROA), bond securities and maturity affect on the bond rating. This shows that liquidity, leverage, profitability, bond securities, and maturity have an impact on bond ratings for bond issuer’s entities.